2023
DOI: 10.1093/cz/zoad045
|View full text |Cite
|
Sign up to set email alerts
|

The roles of different gene expression regulators in acoustic variation in the intermediate horseshoe bat revealed by long-read and short-read RNA sequencing data

Qianqian Li,
Jianyu Wu,
Xiuguang Mao

Abstract: Gene expression changes contribute greatly to phenotypic variations in nature. Studying patterns of regulators of gene expression is important to fully understand the molecular mechanism underlying phenotypic variations. In horseshoe bats, the cochleae are finely tuned to echoes of call frequency. Here, using 2 recently diverged subspecies of the intermediate horseshoe bat (Rhinolophus affinis hainanus and R. a. himalayanus) with great acoustic variations as the system, we aim to explore relative roles of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 108 publications
0
1
0
Order By: Relevance
“…This mainly resulted from the different methods used between studies (rMATs in [40]; DEXSeq in this study). Another recent study that used both rMATs and DEXSeq when performing AS analysis in the same tissue revealed that the former method detected much more ASGs than the latter [73] (1932 with rMATs and 1267 with DEXSeq). Nevertheless, our current study and [40] in diverse bat species and tissues support an important role of AS in encoding sexual differences [36,39,74,75].…”
Section: Discussionmentioning
confidence: 99%
“…This mainly resulted from the different methods used between studies (rMATs in [40]; DEXSeq in this study). Another recent study that used both rMATs and DEXSeq when performing AS analysis in the same tissue revealed that the former method detected much more ASGs than the latter [73] (1932 with rMATs and 1267 with DEXSeq). Nevertheless, our current study and [40] in diverse bat species and tissues support an important role of AS in encoding sexual differences [36,39,74,75].…”
Section: Discussionmentioning
confidence: 99%